2021
DOI: 10.24136/eq.2021.019
|View full text |Cite
|
Sign up to set email alerts
|

Does income inequality matter for CO2 emissions in Russian regions?

Abstract: Research background: Intensive economic growth in Russian regions during recent decades has been associated with numerous environmental issues, particularly increasing CO2 emissions, as well as income inequality. To achieve sustainable development, it is necessary to resolve these issues. Purpose of the article: To shed light on the impact of income inequality on CO2 emissions based on Russian regional data covering the years 2004?2018. Methods: Gini index and decile dispersion ratio are used to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…This made businesses consider the impacts of all activities economically, environmentally and socially to ensure a greener way of life both now and in the future. This enables linking economic activities with social and environmental values to sustain well-being for future generations rather than limiting all activities to financial gain to the detriment of environmental standards (Tiba et al, 2021;Davidson et al, 2021). It is needed to provide solutions to environmental problems rather than adding to the existing ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This made businesses consider the impacts of all activities economically, environmentally and socially to ensure a greener way of life both now and in the future. This enables linking economic activities with social and environmental values to sustain well-being for future generations rather than limiting all activities to financial gain to the detriment of environmental standards (Tiba et al, 2021;Davidson et al, 2021). It is needed to provide solutions to environmental problems rather than adding to the existing ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While ETS provides sustainable, dynamic economic incentives for corporate technological innovation and promotes investment in emission-reducing technologies. From the international perspective, especially if accompanied by the use of environmental technologies, the CO 2 emissions will be reduced (Davidson et al, 2021) [ 2 ]. Therefore, as a profit-seeking enterprise, funds are increasingly invested in green and environmental innovation (Ionescu, 2021) [ 28 ], and it will improve its resource allocation efficiency through technological innovation (Bu et al, 2020) [ 29 ].…”
Section: Background Of Pilot Ets and Research Hypothesismentioning
confidence: 99%
“…Excessive greenhouse gases emissions have massively compromised the sustainability of the natural world and economy (Ionescu, 2021; Davidson et al, 2021) [ 1 , 2 ], faced with multiple challenges such as the climate crisis and environmental pollution, countries around the world are actively exploring energy conservation and emission reduction policies (Zheng et al, 2020; Qian et al, 2021) [ 3 , 4 ], and the transition to an environmentally friendly society necessitates the establishment of low-carbon policies that meets the economic development in line with sustainable goals (Ionescu, 2021) [ 1 ]. China has become the world’s largest energy consumer and carbon emitter (IEA, 2014) [ 5 ], with plans to reach a carbon peak by 2030 and be carbon neutral by 2060.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the EKC hypothesis' projected economic expansion eventually leads to a decrease in pollution (CH4 emissions) after reaching a particular higher level; Apergis et al (2017), that the EKC hypothesis occurs in 10 US states; Cahyadin et al (2021), revealed that traditional EKC occurred in 97 developing countries during the period 1991-2014; Chen & Taylor (2020), assessed environmental quality in Singapore from 1900 to 2017 in the context of economic development and related phenomena utilizing heavy metals (chromium, Cr). After conducting an econometric study, the National Emissions Inventory (NEI) as-sessment determined that Singapore's Cr emission history is consistent with the EKC; Davidson et al (2021), based on dynamic data panel estimates with GMM and Russian regional data for 2004-2018, the EKC hypothesis was validated, implying an inverted U-shaped economic relationship between regional growth and CO2 emissions; Fasikha & Yuliadi (2018), that ASEAN country during the period 2005-2015 indicated the EKC hypothesis; Koirala & Mysami (2015), testing the inverted U-shaped EKC hypothesis was successful at the district level in the US using information on the net impact of forest resources on CO2 emissions and per capita income; Tiba & Frikha (2020), investigates a modified Kuznets curve for the environment that considers governance and human development factors affecting macroeconomic sustainability. That for the modified version of the EKC, the presumptive EKC hypothesis is confirmed.…”
Section: Environment and Hypothesis Environmental Kuznets Curve (Ekc)...mentioning
confidence: 99%